A CROSS SECTIONAL STUDY ON THE CHOICES OF FEMALE MEDICAL STUDENTS IN SELECTION OF THEIR FUTURE SPECIALTIES - Sabiha, Zia-Ul-Ain; Adnan, Shakira; Khaliq, Hina; Irfan, Muhammad (Journal of Postgraduate Medical Institute, 2016)
Objectives: To find out the choices of female medical students in selection of their future specialties and to study the factors influencing their decision. Methodology: This cross-sectional study was conducted among public & private sector medical colleges of Peshawar including Khyber Medical College (KMC), Rahman Medical College (RMC), Peshawar Medical College (PMC) & Kabir Medical College (KaMC). A semi structured questionnaire based on the objectives was distributed among the students to collect their responses. Frequencies were calculated for all the variables including demographic and objective specific variables for the study. Results: A total of 300 female students gave their responses out of 333, who were given the questionnaire. Regarding the specialty of their personal interest, 90(30%) students answered surgery and allied, 110(36.67%) medicine & allied while 70(23.33%) females selected obstetrics & gynaecology as their specialty of choice. The choice was mainly driven by personal interest [n=189 (65.85%)] and inspiration from a role model [n=36 (12.54%)]. Out of these 300, 85 students were not sure if they will be working in the specialty of their personal interest or not, due to many reasons including whether they will be able to adjust work-life balance [n=21 (24.71%)] and difficulty in the exams of specialty of choice [n=18 (21.18%)]. Conclusion: A large number of female students selected medicine and allied as their choice specialty. The choice was mostly driven by personal interest. There were almost a quarter of students who were not sure whether they will be working in the specialty of choice due to various reasons.